PENINGKATAN INTERAKSI EDUKATIF DAN HASIL BELAJAR MENGGUNAKAN METODE ROLE PLAYING PADA PEMBELAJARAN PKN - Riti Riyani, Enris Erif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to determine the increase of educational interaction and learning outcome of student using the method of role playing in grade IV SDS Al Madani South East Pontianak. The research method that been used was descriptive method with type of Classroom Action Research. This research was done 3 cycles. The result of research were obtined (1) The ability of teacher to prepare lesson plan from cycle I was 2,014, cycle II 2,648, cycle III 3,782. (2) The ability of teachers in implementing the learning increase from cycle I 2,415, cycle II 3,165, cycle III 3,915. (3) Educational interaction of student increase from cycle I 20,49%, cycle II 39,022%, cycle III 50,72%. (4) The average of learning outcome of student incrased from cycle I 77,56, cycle II 81,34, cycle III 86,70. The using role playing can echance student educational interaction and result of student learning outcome. Keywords: Educational Interaction, The Learning Outcome, Role Playing Method